2013
DOI: 10.1002/ejic.201300656
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)–imida‐salen Complexes Encapsulated into NaY Zeolite for Oxidations Reactions

Abstract: The oxidation of phenol, cychohexanol and hydroquinone has been screened in the presence of copper(II) complexes with the Schiff‐base salen ligand, 1,5‐bis[(E)‐5‐chloro‐2‐hydroxybenzylideneamino]‐1H‐imidazole‐4‐carbonitrile, and encapsulated into NaY zeolite by using two different methods. The new heterogeneous catalysts were characterized by SEM, XRD, FTIR, EPR and Raman spectroscopy as well as by chemical analysis. The structures of the copper(II) complexes were proposed on the basis of theoretical studies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 77 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Probably, the manganese in NaY is located in the framework sites inaccessible to the ligand [22,23]. Migration of some metal ions from the supercages to the sodalite cages was reported in the literature [19,24]. The similar C/N ratio found (3.16) relates to the free complex (3.43) suggesting, that the organic ligand maintained its structure after encapsulation.…”
Section: Resultsmentioning
confidence: 74%
“…Probably, the manganese in NaY is located in the framework sites inaccessible to the ligand [22,23]. Migration of some metal ions from the supercages to the sodalite cages was reported in the literature [19,24]. The similar C/N ratio found (3.16) relates to the free complex (3.43) suggesting, that the organic ligand maintained its structure after encapsulation.…”
Section: Resultsmentioning
confidence: 74%
“…Similar FTIR spectra and different intensities of peaks on encapsulation and hydrogenation of the complexes were observed, which were in agreement with the XRD analysis. Further conclusive evidence of the successful encapsulation of Cu([H 2 ]salen), Cu([H 4 ]salen) into the NaY was shown by the appearance of the band at 568 cm 21 (CoAN), 470 cm 21 (CoAO), 1500-1600 cm 21 (aromatic ring), 1500-1200 cm 21 (CAN for [H 4 ]salen) [23,24] (Figure 3). Figure 4 also confirmed the small change in geometry and stability of Cu(II) [H 4 ]salen and [H 2 ]salen complexes due to encapsulation and hydrogenation.…”
Section: Characterization Of the Catalystmentioning
confidence: 86%
“…However, the amount of copper was higher in sample obtained by "IM" than the "SB" method probably due to higher retention inside the supercage for complex obtained by "IM" during the synthesis [19]. Significant decrease in the surface area (S BET ) and the pore volume (V BJH ) as well as the pore diameter (D BET ]salen complexes encapsulated within NaY revealed that the complexes were structurally unaltered after the encapsulation procedure ( Figure 2) [21]. Moreover, the relative intensities of the prominent diffraction peaks decreased after the introduction of complex mainly due to contrast matching between the NaY framework and organic moieties which were located inside the channels of the support [22].…”
Section: Characterization Of the Catalystmentioning
confidence: 89%
See 1 more Smart Citation
“…1). 29 3.1.2 FTIR. The characterization of neat and encapsulated complexes by FTIR spectroscopy was analysed in comparison (Fig.…”
Section: Analytical Methods Of Pulpmentioning
confidence: 99%